2017
DOI: 10.15376/biores.12.3.6011-6023
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Process Parameters on the Density Profile and Hardness of Surface-densified Birch Wood (Betula pendula Roth)

Abstract: This study examined the influence of temperature and time of treatment on the density profile and hardness of surface-densified birch wood (Betula pendula Roth). An analysis of the wood density profile was conducted on the basis of the following parameters: thickness, maximum density, and the distance between the maximum density and the wood surface. Depending on the technological parameters' values, the degree of compression of the wood was 13% to 22%, and its maximum density was 808 kg/m 3 to 994 kg/m 3 . As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 19 publications
1
13
0
3
Order By: Relevance
“…As well known, many studies investigated various compression Table 1 The band intensity and ratio of pristine wood (PW) and densified wood (DW) a and b values indicate the intensity ratio of the absorption band and the maximum absorption band near 1027 cm −1 in that curve ratios of densified wood under different processing conditions. It was reported that the compression ratio was generally lower than 30% after the densification without any chemical pretreatment [33,34]. However, in this work, the average compression ratio was approximately 80% in the radial direction of wood.…”
Section: Ftir Analysismentioning
confidence: 49%
“…As well known, many studies investigated various compression Table 1 The band intensity and ratio of pristine wood (PW) and densified wood (DW) a and b values indicate the intensity ratio of the absorption band and the maximum absorption band near 1027 cm −1 in that curve ratios of densified wood under different processing conditions. It was reported that the compression ratio was generally lower than 30% after the densification without any chemical pretreatment [33,34]. However, in this work, the average compression ratio was approximately 80% in the radial direction of wood.…”
Section: Ftir Analysismentioning
confidence: 49%
“…Among these processes, densification is obtained by compressing wood in transverse direction causing cell lumina to obliterate and wood density to increase [3]. The increased wood density should then translate into increased wood mechanical performances [4][5][6][7][8][9]. Densification by compression can be preceded by heating wood at high temperatures [10], or softening it with hot steam [2,11,12] or by chemical treatments or impregnation with resins [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Wood densification improves the physical and mechanical properties of solid wood by increasing the wood density via reducing the void volume of the lumens [1][2][3]. Most studies on wood densification refer to wood surface densification, which is generally achieved by surface pressing at high temperatures (higher than 140 °C) after long terms of conditioning for uniform moisture distribution or after water spraying on surfaces [4][5][6][7][8][9]. However, the position and thickness of the compressed layer(s) are not controllable.…”
Section: Introductionmentioning
confidence: 99%